Terminal sequences of vesicular stomatitis virus RNA are both complementary and conserved. - Keene, J D (1979)
The nucleotide sequences at the 5' and 3' termini of RNA isolated from the New Jersey serotype of vesicular stomatitis virus [vsV(NJ)] and two of its defective interfering (DI) particles have been determined. The sequence differs from that previously demonstrated for the RNA from the Indiana serotype of VSV at only 1 of the first 17 positions from the 3' terminus and at only 2 of the first 17 positions from the 5' terminus. The 5'-terminal sequence of VSV(NJ) RNA is the complement of the 3'-terminal sequence, and duplexes which are 20 bases long and contain the 3' and 5' termini have been isolated from this RNA. The RNAs isolated from DI particles of VSV(NJ) have the same base sequences as do the RNAs from the parental virus. These results are in sharp contrast to those obtained with the Indiana serotype of VSV and its DI particles, in which the 3'-terminal sequences differ in 3 positions within the first 17. However, with both serotypes, the 3'-terminal sequence of the DI RNA is the complement of the 5'-terminal sequence of the RNA from the infectious virus. These findings suggest that the 3' and 5' RNA termini are highly conserved in both serotypes and that the 3' terminus of DI RNA is ultimately derived by copying the 5' end of the VSV genome, as recently proposed (D. Kolakofsky, M. Leppert, and L. Kort, in B. W. J. Mahy and R. D. Barry, ed., Negative-Strand Virus and the Host Cell, 1977; M. Leppert, L. Kort, and D. Kolakofsky, Cell 12:539-552, 1977; A. S. Huang, Bacteriol. Rev. 41:811-8218 1977).